2013
DOI: 10.5951/mathteacmiddscho.19.3.0148
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Spots and Developing Multiplicative Sense Making

Abstract: Seeing Spots Cans on a grocery store shelf and Hirst's Capric Acid Amide can illustrate dot arrays, thus helping students understand the distributive property, partial products, and the standard algorithm for multiplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…There appear to be some clear links between the use of the array, an understanding of place value partitioning (Jazby & Pearn, 2015), and the distributive property (Matney & Daugherty, 2013;Kinzer & Stafford, 2015). Similarly, it is reasonable to suggest that the base ten property of place value underpins the use of extended number facts (Ross, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…There appear to be some clear links between the use of the array, an understanding of place value partitioning (Jazby & Pearn, 2015), and the distributive property (Matney & Daugherty, 2013;Kinzer & Stafford, 2015). Similarly, it is reasonable to suggest that the base ten property of place value underpins the use of extended number facts (Ross, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It was noted earlier that the proportion of Year 6 students who drew an array was less than for the Year 5s and it was suggested that this might be due to a progressive lessening in the use of the array with older students. However, as discussed earlier (Benson et al, 2013;Matney & Daugherty, 2013), the array underpins the distributive property which in turn underpins the grid method and written multiplication algorithm. It is possible that these students have been taught to use the algorithm without being exposed to its progressive development from the array to the grid method.…”
Section: Use Of the Array To Show 4 ×mentioning
confidence: 99%
See 1 more Smart Citation
“…For this to occur, teachers need to understand how and why the array is important. Matney and Daugherty (2013) are very clear about the power of the array to help students visualize mathematical structures like commutativity and distributivity, adding that students' computational errors may be compounded by their lack of understanding of what they are doing. They note that students are better able to understand commutativity when they rotate the array through ninety degrees.…”
Section: Arrays and Equal Groupsmentioning
confidence: 99%